2011
DOI: 10.1002/adma.201003600
|View full text |Cite
|
Sign up to set email alerts
|

A New Femtosecond Laser‐Based Tomography Technique for Multiphase Materials

Abstract: A new tomography technique for image 3D nm‐scale material features in mm3 volumes has been developed. The technique employs a femtosecond laser for layer‐by‐layer material removal at rates 4–5 orders of magnitude faster than comparable serial sectioning techniques. The technique can be applied to a wide range of multiphase materia ls and an example of its application for imaging of TiN particles inhomogeneously dispersed in a metallic matrix is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…A similar laser has previously been employed for development of a optical tomography approach described as the femtsecond laser-based tomography technique (FSLTT) technique. 12 The CPA-2110 has an average power of 1.2 W, 1 kHz repetition rate, 780 nm wavelength, and uses a Ti-sapphire crystal as the primary gain medium. Our recent experiments have demonstrated that femtosecond lasers can ablate material with low amounts of collateral damage 22 and a negligible heat affected zone.…”
Section: B Femtosecond Lasermentioning
confidence: 99%
See 1 more Smart Citation
“…A similar laser has previously been employed for development of a optical tomography approach described as the femtsecond laser-based tomography technique (FSLTT) technique. 12 The CPA-2110 has an average power of 1.2 W, 1 kHz repetition rate, 780 nm wavelength, and uses a Ti-sapphire crystal as the primary gain medium. Our recent experiments have demonstrated that femtosecond lasers can ablate material with low amounts of collateral damage 22 and a negligible heat affected zone.…”
Section: B Femtosecond Lasermentioning
confidence: 99%
“…We have recently demonstrated that femtosecond lasers can serve as a powerful tool for rapid acquisition of 3D data using optical imaging in an ambient laboratory air environment. 12 The femtosecond laser has proved to be a unique tool for the μm-scale modification of materials due to its low peripheral damage and impressive material removal rates. [13][14][15] However, the limitations of optical imaging constrain the range of material features that can be examined via femtosecond laser serial sectioning in ambient air.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of the material for serial sectioning can be performed with different methods: e.g. by mechanical polishing, electropolishing, focused ion beam (FIB) removal and femtosecond laser ablation (Echlin et al, 2011). Regardless of the method employed for the preparation of the sections, the serial sectioning technique suffers from the misalignment between consecutive sections, which needs to be accurately corrected before further data processing (Uchic, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[29]) or laser ablation (e.g. [30]). One of the advantages with FIB and laser ablation is a relatively high resolution (down to a few nanometres at the best) for each milling layer, thanks to the high precision of the beam.…”
Section: D (X Y Z) Static Characterizationsmentioning
confidence: 99%